2017
DOI: 10.7150/thno.17558
|View full text |Cite
|
Sign up to set email alerts
|

A Crucial Role of CXCL14 for Promoting Regulatory T Cells Activation in Stroke

Abstract: Inflammatory processes have a detrimental role in the pathophysiology of ischemic stroke. However, little is known about the endogenous anti-inflammatory mechanisms in ischemic brain. Here, we identify CXCL14 as a critical mediator of these mechanisms. CXCL14 levels were upregulated in the ischemic brains of humans and rodents. Moreover, hypoxia inducible factor-1α (HIF-1α) drives hypoxia- or cerebral ischemia (CI)-dependent CXCL14 expression via directly binding to the CXCL14 promoter. Depletion of CXCL14 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 81 publications
(106 reference statements)
2
29
0
1
Order By: Relevance
“…In addition, TGF‐β is unlikely the only cytokine that promotes Treg accumulation in hypoxic tumor. In a study of Treg activation by ischemic stroke, HIF‐1α was shown to bind the CXCL14 promoter and drive hypoxia‐dependent CXCL14 expression, with CXCL14 promoting the accumulation of Tregs in the ischemic brain . This study has revealed a new mechanism by which HIF‐1α expression in hypoxic brain cells leads to Tregs recruitment.…”
Section: Regulation Of Tregs By Hif‐1α In Dendritic Cells and Tumor Cmentioning
confidence: 91%
“…In addition, TGF‐β is unlikely the only cytokine that promotes Treg accumulation in hypoxic tumor. In a study of Treg activation by ischemic stroke, HIF‐1α was shown to bind the CXCL14 promoter and drive hypoxia‐dependent CXCL14 expression, with CXCL14 promoting the accumulation of Tregs in the ischemic brain . This study has revealed a new mechanism by which HIF‐1α expression in hypoxic brain cells leads to Tregs recruitment.…”
Section: Regulation Of Tregs By Hif‐1α In Dendritic Cells and Tumor Cmentioning
confidence: 91%
“…Lee et al . also suggested that CXCL14 can promote Treg differentiation and activation . In contrast, Kleinshnitz et al .…”
Section: Lymphocytes Encompass Adaptive Immune‐mediated Responses Folmentioning
confidence: 94%
“…108 Lee et al also suggested that CXCL14 can promote Treg differentiation and activation. 109 In contrast, Kleinshnitz et al surprisingly showed that depletion of Treg cells using the DEREG mouse model reduces brain infarct size, suggesting that Treg cells can further brain damage by inducing BBB dysfunction. 110 Currently, the Treg cell contribution to ischaemic brain damage is still a highly debated topic.…”
Section: Lymphocytes Encompass Adaptive Immunemediated Responses Follmentioning
confidence: 96%
“…We decided to validate it by using qPCR and IHC, and showed concordance between the array results and the results obtained with these two techniques. This cytokine is implicated in the homeostasis of monocyte‐derived macrophages rather than in inflammation and in recruitment of immature dendritic cells and regulatory T cells and in blocking of endothelial cell chemotaxis . Moreover, hypoxia‐inducible factor‐1α and nitric oxide synthase 1 (NOS1) activate CXCL14, whereas inflammatory stimuli such as bacterial lipopolysaccharides block CXCL14 activity .…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine is implicated in the homeostasis of monocyte-derived macrophages rather than in inflammation and in recruitment of immature dendritic cells and regulatory T cells and in blocking of endothelial cell chemotaxis. [32][33][34] Moreover, hypoxia-inducible factor-1a and nitric oxide synthase 1 (NOS1) activate CXCL14, 35 whereas inflammatory stimuli such as bacterial lipopolysaccharides block CXCL14 activity. 36,37 Taken together, these findings suggest that antiangiogenic therapy 38 or NOS1 inhibitors could be potential therapeutic approaches for activating the immune system against SAC.…”
Section: Discussionmentioning
confidence: 99%